Underlying the influencing factors behind the heterogeneous change of urban landscape patterns since 1990: A multiple dimension analysis. (July 2022) - Deng, Longyun; Zhang, Qin; Cheng, Yu; Cao, Qian; Wang, Zheye; Wu, Quanyuan; Qiao, Jianmin
Highlights: At the early stage, urban landscape was regular in shape and highly fragmented. Small patches of urban land were connected into large patches through urban expansion. The shape complexity of eastern cities and megacities first increased and then dropped. Tertiary industry was the main factor affecting the increase in urban land area. Heterogeneous measures should be considered for future urban landscape planning. Abstract: Urbanization brings dramatic changes in land cover and significantly alters urban morphology, which in turn affects the urban ecological processes and environment. To promote urban sustainability, it is necessary to accurately quantify dynamic changes in urban form and reveal the associated influencing factors. This study selected seven periods of urban boundary data and socioeconomic data for 31 provincial capitals in China from 1990 to 2018. The evolution characteristics and influencing factors of urban landscape patterns in different dimensions were analyzed based on stepwise regression method. Results indicated that the patch area and aggregation of urban land showed a significant increasing trend from 1990 to 2018, whereas the landscape fragmentation exhibited a significant decreasing trend. The shape complexity of each city showed an increasing trend from 1990 to 2005, and that of eastern cities and megacities tended to decrease thereafter. This suggest that when urban development reaches a certain level, landscape shape will gradually become regular. There was obvious spatial heterogeneity in the influencing factors of urban landscape pattern evolution. Social and economic development promoted urban expansion whereas reduced urban fragmentation, resulted a negative effect on patch density. For the economically developed cities in the east, after 2005, the urban form has tended to be regularized, and the further increase of the output value of tertiary industry will reduce the landscape shape index (LSI). Urbanization rate played major role in contagion for megacities and other cities were mainly influenced by fixed-asset investment. Therefore, heterogeneous measures should be considered for future urban landscape pattern optimization at various economic zone or hierarchical city scales.